Impact of Fintech on the economic growth: evidence from selected countries - Putri Farhan Najwa, Megat Daud (2018)
Fintech or financial technology is a mix of two words between financial and technology and can be literally defined as the usage of technology to convey financial responses in the financial segment. Previously for the past of two decades, the continuing application and dispersion of the Internet and online business also advancement in information technology (IT) have fundamentally modified the global economy activity. The motivation of the study is to investigate an individual impact that mobile cellular as proxy for Fintech contributed to the growth of economy as logicality of the technology as far as changing the way economic activity is composed recommends that mobile telecommunications has highlights of what is mentioned to be a general useful technology. Furthermore, the significance use of Fintech in the economy might affected the other macroeconomic variables such as the availability of labor force due to technological advancements that bringing down the cost for machinery and equipment as compared to labor cost, which motivated the business to change from human labor to capital. Hence, this study aim to disentangle the two possible relationship, that is the relationship of Fintech and the economic growth and the relationship between Fintech with other macroeconomic variables. This study examines the relationship between Fintech and economic growth through several econometric analyses by using the panel data of nineteen selected countries for year 1988-2015. In this study, a general production function is employed in which gross domestic product (GDP) is used to represent economic growth and mobile cellular subscriptions to represents Fintech. There are also other variables such as total population and energy consumption used as independent variables. In order to answer the objectives of the study, the method to be employed are Panel Ordinary Least Squares (POLS) which to estimate how dependent variable reacts when there is an increase in independent variables, Granger causality test is to determine the direction of causality between all variables and panel ARDL model is perform to determine whether there is the long-run relationship between financial technology (Fintech) and the growth. The finding of the study is consistent the Schumpeter theory that highlight the importance of technological development to boost the economic growth. Based on empirical findings, there is exist a long relationship between Fintech and the economic growth. Besides, the estimated result show that other independent variables such as energy consumption exists bidirectional causality with Fintech in the long run, meanwhile it exists unidirectional causality relationship between population and Fintech in the long run. In addition, the empirical evidence based on ARDL showed that Fintech has long-run relationship with economic growth. The long-run relationship exist between Fintech and the economy growth highlighted that it would be the government’s role to enhance the population productivity by encourage to engage in online transaction as it has opportunity in improving and growing the economy. The government should invest in Fintech companies that provide such technological advancement as it would be interesting in adopting the Fintech across the countries.